2017
DOI: 10.1097/j.pain.0000000000001023
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions that target sleep reduce pain catastrophizing in knee osteoarthritis

Abstract: Pain catastrophizing is a significant risk factor for patients with knee osteoarthritis (KOA) and thus is a target for many psychological interventions for pain. This study examined if interventions targeting sleep found to be effective in improving sleep in KOA also reduce pain catastrophizing measured as a trait through the pain catastrophizing scale and measured as a daytime and nocturnal state through daily diaries. Secondary analyses were conducted on data collected as part of a randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…In addition to pharmacological sleep modulation, it is imperative to investigate nonpharmacological perioperative sleep‐modulating measures. For example, cognitive behavioral therapy for insomnia (CBT‐I) is effective for relieving sleep problems, and for relieving comorbid insomnia associated with chronic pain . In an intensive care unit setting, nonpharmacological sleep‐promoting measures such as earplugs and eye masks may improve sleep and decrease the incidence of delirium .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pharmacological sleep modulation, it is imperative to investigate nonpharmacological perioperative sleep‐modulating measures. For example, cognitive behavioral therapy for insomnia (CBT‐I) is effective for relieving sleep problems, and for relieving comorbid insomnia associated with chronic pain . In an intensive care unit setting, nonpharmacological sleep‐promoting measures such as earplugs and eye masks may improve sleep and decrease the incidence of delirium .…”
Section: Discussionmentioning
confidence: 99%
“…Pain management was a great concern for doctors in treating knee OA [ 19 , 20 ]. VAS scale was most reported to evaluate pain intensity (4 trials, n = 261) in the selected studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from previous studies suggest that sleep problems may modify the relationship between PA and pain through their effect on psychosocial factors and pain processing. Several studies have suggested that sleep problems are associated with psychosocial problems (e.g., catastrophizing, anxiety) and abnormalities in the central nervous system (CNS) pain processing 42,43 . People who report restless sleep may be more likely to have psychosocial problems and abnormalities in CNS pain processing.…”
Section: Discussionmentioning
confidence: 99%